Effectiveness of Ecotourism-Based Entrepreneurship Education as Seen from Students' Perception - Januardi; Reina Damayanti; Linda (Graduate Program Magister Manajemen Pendidikan, 2026)
The global climate crisis demands a radical transformation in the higher education sector, particularly in entrepreneurship curricula. Students, as agents of change, no longer view business solely as an instrument of capital accumulation, but rather as a means of conservation. Ecotourism has emerged as an ideal laboratory for testing the synergy between profitability and environmental preservation. However, the effectiveness of this education depends heavily on how students perceive the relevance of the material to the realities of the field. Understanding their perspectives is crucial to evaluating whether current learning models are capable of producing competent ecopreneurs or merely providing theoretical insights without any real impact on ecosystem sustainability and the well-being of local communities.